2016
DOI: 10.3823/2002
|View full text |Cite
|
Sign up to set email alerts
|

Profile of caregivers of institutionalized elders

Abstract: Introduction: The aging process of the population causes several transformations in social, cultural and health context. The demand for gerontological care increases and, due to that, homes for the aged emerge as an alternative housing for elders who do not have enough support at this new life stage or for those whoopt to live there.Objective: This study aimed at describing the profile of caregivers of elderly people who live in homes for the aged in the metropolitan regionof João Pessoa, Paraíba, Brazil.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Dentre os achados, a feminização do cuidado se destacou como um ponto importante. Ao longo dos anos, culturalmente e socialmente, as mulheres são impostas no papel de cuidadoras, tanto no seu âmbito familiar quanto no institucional, onde o homem é responsável pelas atividades fora de casa, o provedor do lar, e a mulher às atividades domésticas (LIMA et al, 2016;ZENG et al, 2019;MELO et al, 2022).…”
Section: Discussionunclassified
“…Dentre os achados, a feminização do cuidado se destacou como um ponto importante. Ao longo dos anos, culturalmente e socialmente, as mulheres são impostas no papel de cuidadoras, tanto no seu âmbito familiar quanto no institucional, onde o homem é responsável pelas atividades fora de casa, o provedor do lar, e a mulher às atividades domésticas (LIMA et al, 2016;ZENG et al, 2019;MELO et al, 2022).…”
Section: Discussionunclassified
“…Historicamente, ao longo dos anos, as mulheres exercem o papel principal de cuidador da família e dos filhos, seja no ambiente familiar ou institucional, o que pode inclusive contribuir para a humanização do cuidado. Percebe-se que esse aspecto é tão forte que, por vezes, ele é atribuído à mulher quase como uma obrigação, pois cabe ao homem o lugar de provedor do lar e à mulher exercer o ato de cuidar (Lima et al, 2016;Maciel et al, 2021;Zeng et al, 2019;Ziesemer et al, 2020).…”
Section: Discussionunclassified
“…Similar studies in South Africa and Brazil found that formal caregivers of older adultss working in long-term care settings as paraprofessionals do not have adequate training. They are easily hired, without any screening for physical and emotional prerequisites for their older adults caregiving duties (Lima et al, 2016;Mehta & Leng, 2017;Ngubeni, 2011). Formal caregivers in developing nations likewise face poor personal care (Mehta & Leng, 2017), deteriorated physical and emotional well-being (Goh et al, 2013), and struggles with eating and sleeping (Czuba, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though Cattell (1993) called attention to waning family supports in Sub-Saharan Africa nearly 30 years ago, organized care and social services for older adults remain lacking. Elders who have care needs that exceed the capabilities of their families or who lack family support will increase the demand for residential long-term care (Lima et al, 2016).…”
Section: "It Is All About Giving Priority To Elders' Needs:" Challeng...mentioning
confidence: 99%